Concentrated Manipueira as an Alternative Low-Cost Substrate to Rhodotorula glutinis for Biotechnological Production of High Contents of Carotenoids - Felipe de Andrade Maia; Willen Silva Igreja; Ana Augusta Odorissi Xavier; Adriana Zerlotti Mercadante; Alessandra Santos Lopes; Renan Campos Chisté (Fermentation, 2023)
Carotenoids are fat-soluble bioactive compounds found in plants, animals, and microorganisms, which have a range of health benefits and great technological and industrial importance in the fields of pharmaceuticals, food, and biotechnology. Yeasts of the genus Rhodotorula can biosynthesize large amounts of carotenoids under environmental stress conditions, and this process may become industrially feasible if production costs are minimized using low-cost by-products as nutrient sources. As cassava roots are produced and consumed in large quantities in the Amazon biome, our research aimed to investigate the best cultivation conditions in a benchtop bioreactor for the biotechnological production of carotenoids by R. glutinis using manipueira as a low-cost substrate. Manipueira is wastewater generated during cassava flour production, and it was concentrated at 12 °Brix for this study. In addition, the carotenoid composition, at the best cultivation condition, was analyzed by LC-MS. Higher carotenoid contents (1410 μg/g of dried biomass) than described in the literature, and biomass (10 g), were produced by R. glutinis using concentrated manipueira as a low-cost substrate after cultivation at pH 5, 35 °C and agitation at 150 rpm. At the best cultivation conditions, β-carotene, lutein, and 5,8-epoxy-lutein were the major carotenoids, with the latter two compounds being identified for the first time in the biomass of R. glutinis. Therefore, concentrated manipueira can be seen as a feasible alternative and low-cost substrate to be used for the biotechnological production of high carotenoid contents by R. glutinis.